Pengaruh matrik resin-epoxy terhadap kekuatan impak dan sifat fisis komposit serat nanas - Ade Irvan Tauvana; Syafrizal Syafrizal; Mokhamad Is Subekti (Jurnal POLIMESIN, 2020)
Pineapple leaf fiber is currently widely used in furniture and handicraft industries because it is easy to obtain, inexpensive, does not endanger health, can reduce environmental pollution so that later on as a composite reinforcing fiber can overcome environmental problems The choice of epoxy resin as a base material is caused the strength and stiffness of Epoxy resins is greater compared to other types of polymers. This study was intended to see the impact strength of pineapple fibers resin-epoxy and the fracture material of the specimen with macro photographs. The test specimens used pineapple fiber with volume fraction, 10%, 30%, 50% and epoxy resin matrix and hardener as hardener. The specimen is made by casting and mica as a mold. Mechanical testing using impact test, Physical test using photo macro structure. The result of the impact study obtained the impact price on the fraction of 50% volume that is equal to 0.76 J / mm2, this occurs because the fraction of fiber volume of 50% in addition to the distribution of the uniform force by the matrix is also supported by the ideal fiber, from the results of the above research In Can the optimum fiber volume fraction is at 50% volume fraction.